La ultraestructura de espermatozoides y su valor en la sistemática de Scleractinia (Cnidaria: Antnozoa) - Steiner, S. C.C. (1998)
The value of sperm ultrastructure in scleractinian systematics was reviewed and reevaluated with the first information about Montastraea cavernosa and Eusmilia fastigiata. While it is possible to identify and distinguish higher taxonomic groups such as the order Scleractinia and the sub-order Archaecoeniina based on sperm morphology, limitations exist in lower taxa of other sub-orders.. For example, species from different families or genera that share the same sexual character (hermaphroditic or dioecious) are very similar in their sperm morphology. This was reconfirmed by the ultrastructural examination of M. cavernosa which has a sperm type only found in dioecious species and which does not resemble the spermatozoa of its hermaphroditic congener M. faveolata. It is suggested that E. fastigiata is dioecious based on its sperm type which was found to be the same as that of M. cavernosa.